2012
DOI: 10.1371/journal.pone.0048725
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ATP-Binding Regions in the RyR1 Ca2+ Release Channel

Abstract: ATP is an important modulator of gating in type 1 ryanodine receptor (RyR1), also known as a Ca2+ release channel in skeletal muscle cells. The activating effect of ATP on this channel is achieved by directly binding to one or more sites on the RyR1 protein. However, the number and location of these sites have yet to be determined. To identify the ATP-binding regions within RyR1 we used 2N3ATP-2′,3′-Biotin-LC-Hydrazone (BioATP-HDZ), a photo-reactive ATP analog to covalently label the channel. We found that Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
1
8
0
4
Order By: Relevance
“…It has been suggested that the last 100 residues of the C-terminal ‘tail’ contribute to the ATP-binding pocket (Popova et al, 2012). We now confirm that this C-terminal segment contains the ATP-binding pocket of RyR1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the last 100 residues of the C-terminal ‘tail’ contribute to the ATP-binding pocket (Popova et al, 2012). We now confirm that this C-terminal segment contains the ATP-binding pocket of RyR1.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanation such as a reduction in the size of the Ca 2+ stores in aged cells could not explain the increased caffeine response and, thus, we can discard it. An intriguing possibility is that the higher activity of ATP synthase in resting aged cells could induce a local ATP increment in the vicinity of the RyR receptors, which are positively modulated by ATP ; to our knowledge, however, there is no supporting evidence.…”
Section: Discussionmentioning
confidence: 90%
“…Contáctenos: rev.med.ucr@gmail.com cuales también se puede unir el Mg 2+ menor afinidad; sin embargo, cuando el Mg aumenta su concentración, de forma neta, se une más a estas proteínas; actuando como un sistema de control antagonista del Ca 2+ [59]. En estados de depleción de Mg 2+ , el Ca más libremente a la troponina por lo que hay contracciones sostenidas tipo calambre [59,60,61].…”
Section: Implicaciones Clínicasunclassified
“…De igual manera, el Mg 2+ controla los niveles de Ca 2+ , por medio de otras vías, ya mencionados, las cuales podrían tener participación en los calambres. El balance entre Ca 2+ /Mg 2+ en gran medida la apertura de los RyR y la liberación de Ca 2+ inducida por Ca 2+ , porque cuanto menores sean las concentraciones de Mg es la sensibilidad del RyR al Ca 2+ , y por lo tanto podrían aparecer calambres [59,60]. También el Mg 2+ regula proteínas de transporte de Ca la SERCA [61].…”
Section: Implicaciones Clínicasunclassified